A systematic review and meta-analysis of the associations between endometriosis and irritable bowel syndrome. (March 2020) - Saidi, Khadija; Sharma, Shantanu; Ohlsson, Bodil
Abstract: Endometriosis and Irritable Bowel Syndrome (IBS) are common conditions among young women of reproductive age. The etiologies to the diseases are uncertain, but multifactorial pathophysiology has been proposed for each of them. Many studies have examined the two conditions separately, but the literature on the associations between endometriosis and IBS is sparse. However, there is an increasing amount of research on how endometriosis patients are likely to also have a diagnosis of IBS. Furthermore, endometriosis shares several features with IBS, such as low-grade inflammation and visceral hypersensitivity. This systematic review summarized published original articles in English that have compared associations between endometriosis and IBS. The inclusion criteria for articles in the review were: i) endometriosis was diagnosed by surgical methods, ii) gastrointestinal symptoms were examined in a structured manner and iii) IBS was diagnosed by Rome criteria. From the initial 254 publications identified on PubMed, Web of Science and EMBASE, 13 fulfilled the criteria and could finally be included in the summary. The findings from the review showed that women diagnosed with endometriosis seem to have a twofold or threefold risk to also fulfill the criteria for IBS. The summary risk estimate of the four studies included in the meta-analysis was 2.39 (95 % confidence interval: 1.83–3.11). In women initially diagnosed with IBS, some studies reported a threefold risk of having an endometriosis diagnosis. Despite the strong associations reported between the two conditions, this review also revealed a gap in adjusting for factors that may have affected the expression of gastrointestinal symptoms, e.g., phases of the menstrual cycle, medication and psychological aspects, which may have interpretation of the reviewed articles' results. The conclusion of this review is that there is a coexistence of gastrointestinal symptoms fulfilling the Rome criteria in patients with endometriosis, but it is uncertain whether there is a true comorbidity between endometriosis and IBS, or whether the gastrointestinal symptomatology in endometriosis depends on medication. Additionally, the adequacy of the Rome criteria to differentiate IBS from the shared symptomatology of other diseases with visceral hypersensitivity must be further evaluated.